Energy based modeling for temperature cycling induced tin silver copper solder interconnect fatigue life. (June 2020) - Chen, Deng Yun; Osterman, Michael; Dasgupta, Abhijit
Abstract: Lead free (LF) solders such as tin silver copper (SAC) and its variations have been used in microelectronic products for the past decade due the Restriction of Hazardous Substances regulation. In use, temperature cycling is a major contributor to the wear-out failure mechanisms of solder joints during the life span of electronics. To predict the reliability of electronic solder joints, a fatigue life model is needed. Currently, strain energy density based models are widely used for solder joint fatigue life estimation. This paper reviews existing LF solder fatigue life models and provides strain energy based life model constants for a variety of LF solder materials. Highlights: A review of current solder joint fatigue model was conducted. Fatigue model constants for SAC solder under temperature cycling were obtained. Model constants were found to be correlated with silver weight content. Both total energy model and partitioned energy model provided reasonal predictions.